Characteristics of patients with neovascular age-related macular degeneration who are non-responders to intravitreal aflibercept. Issue 5 (15th June 2018) - Hara, Chikako; Wakabayashi, Taku; Toyama, Hiroshi; Fukushima, Yoko; Sayanagi, Kaori; Sato, Shigeru; Sakaguchi, Hirokazu; Nishida, Kohji
Abstract : Purpose: To investigate the frequency and patient characteristics that influence anatomic response of intravitreal aflibercept in treatment-naïve neovascular age-related macular degeneration (AMD). Design: Retrospective, interventional, consecutive case series. Methods: Three hundred and sixty-five eyes of 365 patients with AMD who underwent 3 monthly intravitreal aflibercept treatments with follow-up for at least 12 months were investigated. Treatment response was evaluated as follows. Responders were defined as those with complete resolution of exudation, including intraretinal oedema, subretinal fluid and pigment epithelial detachment, or more than a 100 µm decrease of central retinal thickness at 3 months compared with baseline. Non-responders were defined as patients exhibiting an increase in exudation or a decreased central retinal thickness of less than 100 µm. Results: Nineteen (5.2%) of 365 eyes were identified as non-responders. The remaining were responders to intravitreal aflibercept. The non-responders group was significantly associated with choroidal vascular hyperpermeability on indocyanine green angiography and lower frequency of subretinal hyper-reflective materials on optical coherence tomography. The central choroidal thickness at baseline and after 3 monthly injections tended to be thicker in the non-responder group than the responder group, although the differences did not meet statistical significance (p=0.066 and p=0.051, respectively). Additional treatments with either intravitreal ranibizumab or PDT in combination with aflibercept were effective in 15 (79%) of 19 non-responders. Conclusion: Intravitreal aflibercept is effective for treating eye pathology in most naïve AMD cases. However, non-responsiveness may occur in small subgroup of patients with choroidal vascular hyperpermeability.